2016
DOI: 10.1089/apc.2016.0114
|View full text |Cite|
|
Sign up to set email alerts
|

Good Health and Moral Responsibility: Key Concepts Underlying the Interpretation of Treatment as Prevention in South Africa and Zambia Before Rolling Out Universal HIV Testing and Treatment

Abstract: Gauging community responses to the WHO 2015 recommendation to provide antiretroviral treatment (ART) to all people living with HIV (PLHIV) is critical. There is limited qualitative evidence on the acceptability of this Universal Test and Treat (UTT) strategy or community understanding of the impact of ART on reducing HIV transmission, promoted as Treatment as Prevention (TasP). This article explores early understanding of UTT and TasP in 21 urban communities in South Africa and Zambia in 2013 before a communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 31 publications
5
51
0
Order By: Relevance
“…Although a majority of HIV-negative partners were aware of the concepts underlying U = U, there were some who had not heard the message, and many did not believe it. Our findings are comparable to a study conducted in Zambia and South Africa that reported that people were largely unfamiliar with the prevention benefits of HIV treatment [14] and with studies done among gay men who expressed reluctance for condomless sex even after viral suppression [12,13]. Awareness and acceptance of the additional HIV prevention benefit of ART needs to go beyond targeting HIV-positive partners; including HIV-negative partners in U = U discussions could provide motivation for HIV-positive people to adhere to ART.…”
Section: Discussionsupporting
confidence: 83%
“…Although a majority of HIV-negative partners were aware of the concepts underlying U = U, there were some who had not heard the message, and many did not believe it. Our findings are comparable to a study conducted in Zambia and South Africa that reported that people were largely unfamiliar with the prevention benefits of HIV treatment [14] and with studies done among gay men who expressed reluctance for condomless sex even after viral suppression [12,13]. Awareness and acceptance of the additional HIV prevention benefit of ART needs to go beyond targeting HIV-positive partners; including HIV-negative partners in U = U discussions could provide motivation for HIV-positive people to adhere to ART.…”
Section: Discussionsupporting
confidence: 83%
“…Despite community engagement and messaging on the benefits of immediate ART, many people had internalised previous health messaging about treatment being appropriate only for those who were sick, and were cautious about accepting the change in advice [ 38 ]. Therefore, some considered immediate treatment appropriate for those who are ill , pregnant or in a discordant relationship.…”
Section: Resultsmentioning
confidence: 99%
“…The communities included have a total population of ~ 200,000 in the four Zambian communities, and ~ 100,000 in the three South African communities. The social context and HIV services in all the communities in both countries have been described elsewhere [ 38 ]. An ancillary study on stigma was undertaken, which provides additional information on stigma experiences in health facilities and levels of stigma in different communities, also described elsewhere [ 35 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, during the initial selection of the 21 communities in Zambia and South Africa for HPTN 071, rapid qualitative research (termed a Broad Brush Survey [26]) was conducted to gather data on each community, prior to the implementation of the trial intervention. While the results of this work are drawn on in a number of publications [27][28][29][30], this example focuses on the work published by Bond and colleagues in 2016 [31]. For the rapid assessment, a small team of social science researchers spent about two weeks staying in each study community to undertake data collection, using group discussions, key informant interviews and observations.…”
Section: A Utt Intervention Trial In Zambia and Southmentioning
confidence: 99%